Experimental evidence that behavioral nudges in citizen science projects can improve biodiversity data. (19th April 2023) - Callaghan, Corey T; Thompson, Maureen; Woods, Adam; Poore, Alistair G B; Bowler, Diana E; Samonte, Fabrice; Rowley, Jodi J L; Roslan, Nadiah; Kingsford, Richard T; Cornwell, William K; Major, Richard E
Abstract: One way to improve the value of citizen science data for a specific aim is through promoting adaptive sampling, where the marginal value of a citizen science observation is dependent on existing data collected to address a specific question. Adaptive sampling could increase sampling at places or times—using a dynamic and updateable framework—where data are expected to be most informative for a given ecological question or conservation goal. We used an experimental approach to test whether the participants in a popular Australian citizen science project—FrogID—would follow an adaptive sampling protocol aiming to maximize understanding of frog diversity. After a year, our results demonstrated that these citizen science participants were willing to adopt an adaptive sampling protocol, improving the sampling of biodiversity consistent with a specific aim. Such adaptive sampling can increase the value of citizen science data for biodiversity research and open up new avenues for citizen science project design.